DISIPLIN BELAJAR PESERTA DIDIK DI SMP NEGERI 6 KOTA SOLOK - Ega Danysa Putri; Hasnawati Hasnawati; Asri Atuz Zeky (UIN Imam Bonjol Padang, 2022)
This paper is based on the learning discipline of students at SMP Negeri 6 Solok City. This research uses descriptive quantitative method. Questionnaries were distributed to 31 students in grades 8 SMP Negeri 6 Solok City. The fidnings show that students have good learning discipline. However, there are still students who do not have a concern for discipline in learning such as some students who are still not disciplne in their time and actions in learning at school.